2017
DOI: 10.2196/mhealth.8549
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Cardiovascular Disease Mobile Apps’ Information Types, Information Quality, and Interactive Functions for Self-Management: Systematic Review

Abstract: BackgroundChina has a large population with cardiovascular disease (CVD) that requires extensive self-management. Mobile health (mHealth) apps may be a useful tool for CVD self-management. Little is currently known about the types and quality of health information provided in Chinese CVD mobile apps and whether app functions are conducive to promoting CVD self-management.ObjectiveWe undertook a systematic review to evaluate the types and quality of health information provided in Chinese CVD mobile apps and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 51 publications
2
21
0
2
Order By: Relevance
“…However, we found that some apps developed in China provided comprehensive CKD knowledge without describing the reference resources. Other researchers have also raised similar observations in mobile apps for cardiovascular disease in China [ 49 , 53 ]. Although some of these apps seem to provide information or advice regarding diagnosis, prognosis, monitoring, and treatment for HCPs and patients, none of the apps state in their introduction whether their function meets the definition of a medical device.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…However, we found that some apps developed in China provided comprehensive CKD knowledge without describing the reference resources. Other researchers have also raised similar observations in mobile apps for cardiovascular disease in China [ 49 , 53 ]. Although some of these apps seem to provide information or advice regarding diagnosis, prognosis, monitoring, and treatment for HCPs and patients, none of the apps state in their introduction whether their function meets the definition of a medical device.…”
Section: Discussionsupporting
confidence: 60%
“…Each functionality category corresponded to more than 2 aspects. The quality of the information from the mobile apps was analyzed with reference to previous studies [ 36 , 49 ]. Each aspect was regarded as a quality indicator.…”
Section: Methodsmentioning
confidence: 99%
“…Esta praticidade é um fato também observado em outros estudos. 4,[8][9][10][11][12] A segunda é a sensação de maior proximidade médico-paciente. 2 Apesar da proximidade médico-paciente proposta pelo programa, dois pacientes consideraram o aplicativo com os vídeos bastante didático, mas afiramram que a explicação do médico sempre vai agregar mais informações.…”
Section: Discussionunclassified
“…Figure 2 shows the services that can be delivered by mHealth. 545 | P a g e www.ijacsa.thesai.org There are several research have been done to investigate the potential use of mHealth for Cardiovascular disease management [3,4,5,7,8,9,10,11,12,13]. The details explanations for those related research are as follows:…”
Section: Mobile Health Application For Cardiovascularmentioning
confidence: 99%
“… Xie et al [10] mention that mHealth can be used for promoting cardiovascular disease self-management. However in their research, they find thath Chinese cardiovascular apps are insufficient to provide comprehensive health information and interactive functions to facilitate cardiovascular self-management.…”
Section: Mobile Health Application For Cardiovascularmentioning
confidence: 99%